(untitled) (Conferencea, 2023)
A few decades ago, schools had home economics lessons, which later became labor lessons, now for many years this subject has been called “Technology”. Education is perceived by people as the dominant social value of our time: a steady demand for educational services is formed in society, the dynamics of the professional orientations of young people is clearly visible. The lessons of "Technology" at school are the first step towards the professional orientation of young people, especially the working specialties that are relevant today.